2017
DOI: 10.1021/jacs.7b02058
|View full text |Cite
|
Sign up to set email alerts
|

Co-assembly of Peptide Amphiphiles and Lipids into Supramolecular Nanostructures Driven by Anion−π Interactions

Abstract: Co-assembly of binary systems driven by specific non-covalent interactions can greatly expand the structural and functional space of supramolecular nanostructures. We report here on the self-assembly of peptide amphiphiles and fatty acids driven primarily by anion-π interactions. The peptide sequences investigated were functionalized with a perfluorinated phenylalanine residue to promote anion-π interactions with carboxylate headgroups in fatty acids. These interactions were verified here by NMR and circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 64 publications
(101 reference statements)
0
73
0
Order By: Relevance
“…For instance, Zhang and Wang developed a series of noncovalently bonded complexes namely supramolecular amphiphiles capable of self‐organizing into versatile nanoarchitectures . Stupp and co‐workers designed supramolecular nanostructures from the coassembly of peptide amphiphiles and lipids based on their anion–π interactions . Kinetically, factors such as temperature, concentration, pH, and solvent should be considered during the self‐assembly, as these parameters might affect the site and rate of nucleation and growth, as well as corresponding aggregation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang and Wang developed a series of noncovalently bonded complexes namely supramolecular amphiphiles capable of self‐organizing into versatile nanoarchitectures . Stupp and co‐workers designed supramolecular nanostructures from the coassembly of peptide amphiphiles and lipids based on their anion–π interactions . Kinetically, factors such as temperature, concentration, pH, and solvent should be considered during the self‐assembly, as these parameters might affect the site and rate of nucleation and growth, as well as corresponding aggregation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stupp and co‐workers designed peptide amphiphile analogs with same alkyl chains and amino acid sequences but different terminal groups to enhance the hydrogen bonding between components, showing excellent coassembly phenomenon . Recently, they further implanted one fluorinated phenylalanine in peptide sequences to strengthen the anion–π interaction, allowing for successful preparation of peptide/dodecanoic acid binary coassemblies . We found that the coassembly behavior between pyrene and naphthalene dicarboximide appended glutamate building blocks was concentration‐dependent (a kinetic control), and higher concentration would facilitate the coassembly and improve the intercomponent energy transfer .…”
Section: Methodsmentioning
confidence: 92%
“…In other aspect, self-assembled amphiphilic peptide nanostructures have been considered not only as pathological aggregates but also as advanced materials in material sciences [6][7][8]13,14,[23][24][25][26][27]34,[37][38][39][40][41][42][43], such as for biocatalyst [37][38][39][40][41][42][43], stabilizing diverse membrane as a fundamental component [15][16][17][18]. The final function of peptides depends on the self-assembled and properties of hierarchical structures, the mechanisms of peptide aggregation (the driving forces needed to understand) [44][45][46]. Appropriate model systems are indispensable.…”
Section: Discussionmentioning
confidence: 99%